Penegakan Pengawasan Mahkamah Kehormatan Mahkamah Konstitusi Terhadap Hakim Konstitusi - Niken, Niken; Khalid, Khalid (Nagari Law Review, 2023)
This research aims to determine the important role of the Constitutional Court Ethics Council in upholding the integrity and ethics of constitutional judges and in upholding law and justice in Indonesia. "This research examines the position and role and supervision of the Ethics Council in guiding constitutional judges." the behavior of constitutional judges in carrying out their duties as law enforcers and protectors of the constitution. The research methodology used is a descriptive approach, namely analyzing case data in the form of reports and public information regarding alleged violations of the Code of Ethics by constitutional judges. in 2014 and 2015. These data were analyzed to determine the number of cases followed up, recommendations given, as well as the handling process and decisions taken by the Ethics Council. They have received several reports from the public regarding alleged violations of the Code of Ethics by constitutional judges. However, there were no serious sanctions imposed by the Ethics Council in this case. On the other hand, the Honorary Council provides recommendations to the Constitutional Court to improve case handling and judicial procedures. In conclusion, the Ethics Council has an important role in maintaining the integrity and ethics of constitutional judges and upholding law and justice. "The recommendations given by the Honorary Council are very important in improving and perfecting the trial process at the Constitutional Court.